Kemampuan Berpikir Kreatif Matematis Siswa Pada Trigonometri - Dwi Ningsih, Febriyanti; Ristontowi, Ristontowi; Asmara, Adi (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
The point of the inquire about is to decide students' numerical imaginative considering capacities mathematical on trigonometry fabric. The sort of investigate is graphic subjective, the investigate question is understudies at SMA Negeri 1 Central Bengkulu and the inquire about subjects are 33 understudies. The subjects interviewed were 3 students categorized as high, medium and low. Data collection was carried out using test questions and interviews. The research results showed that students' creative thinking abilities averaged 54.10. With a low indicator, namely the originality indicator, there are 22% of students in the high category, 43% of students in the medium category, 34% of students in the low category, and factors that influence low thinking ability are students who don't dare to try new things, forget, rarely practice in working on questions.